Synthesis and biological evaluation of (4-Fluorophenyl)(1-(5-phenyl-1,3,4-oxadiazol-2-yl)indolizin-3-yl)methanone derivatives as anticancer and antimicrobial agents (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
A novel series of (4-Fluorophenyl (1-(5-phenyl-1,3,4-oxadiazol-2-yl)indolizin-3-yl)methanone derivatives 9(a-n) were synthesized by the coupling reaction of 3-(4-fluorobenzoyl)indolizine-1-carboxylic acid and substituted benzohydrazide followed by intramolecular cyclization. The structures of the compounds were characterized by 1H NMR, 13C NMR, LCMS, FT-IR, and elemental analyses. The compounds 9(a-n) anti-cancer activity was evaluated against the MCF-7 cell line (HTB-22, Homo sapiens, Breast carcinoma). Compound 9j (IC50 = 21.57 μM), and 9n (IC50 = 8.52 μM) exhibited the most potent cytotoxicity activity compared with standard drug doxorubicin (IC50= 25.71). The antibacterial activity was evaluated against Staphylococcus aureus ATCC 6538 and Escherichia coli ATCC 8739. The compounds ZOI=16mm) and 9i (ZOI=18 mm) exhibited moderate antibacterial activity compared with standard drug ciprofloxacin. The antifungal activity was evaluated against Candida albicans ATCC 10231. Most compounds exhibited moderate antifungal activity compared with the standard drug Itraconazole.